2007
DOI: 10.1001/archneur.64.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Dopaminergic Drug–Related Pathological Gambling in Parkinson Disease

Abstract: Patients: Twenty-one patients with idiopathic PD with PG after the patients began receiving medications compared with a consecutive sample of 42 patients with idiopathic PD without compulsive behaviors.Main Outcome Measures: Clinical features, comorbid psychiatric and substance use disorders, personality traits, and impulsivity scores.Results: Patients with PG had a younger age at PD onset (P=.006), higher novelty seeking (PϽ.001), medication-induced hypomania or mania (P =.001), impaired planning (P=.002), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
271
4
12

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 295 publications
(317 citation statements)
references
References 17 publications
29
271
4
12
Order By: Relevance
“…92,93 Although PG was initially associated with both DA agonist monotherapy and combination DA agonist and LD therapy, more recent reports indicate that it is combined therapy that is most prominently associated with PG. 94 Although it is reported that PG reverses with decreasing or stopping DA agonists, 95 this has not been a consistent finding. There are also data supporting an association with LD therapy, amantadine, and (although this is not universally supported) deep brain stimulation surgery.…”
Section: Safety Issues: Pathological Gambling and Related Impulse Conmentioning
confidence: 96%
See 4 more Smart Citations
“…92,93 Although PG was initially associated with both DA agonist monotherapy and combination DA agonist and LD therapy, more recent reports indicate that it is combined therapy that is most prominently associated with PG. 94 Although it is reported that PG reverses with decreasing or stopping DA agonists, 95 this has not been a consistent finding. There are also data supporting an association with LD therapy, amantadine, and (although this is not universally supported) deep brain stimulation surgery.…”
Section: Safety Issues: Pathological Gambling and Related Impulse Conmentioning
confidence: 96%
“…86,89,91,92,95 Furthermore, there are increasing data to suggest that PG may be disease-related, with reports of onset without change in medications, lack of relation to agonist dosages, continuing symptoms after stopping DA agonists in a notable portion of cases, spontaneous reversal without medication changes, and particular disease-related risk factors (including young age of onset, longer disease duration, association with prior history of alcoholism and other ICD, mania, executive dysfunction, and novelty seeking). 80,81,86,90,94,96 There are also significant psychiatric and motor comorbidities; depression, disinhibition, irritability, appetite changes and mania or hypomania. 94,97 These have been seen in non-PD cases as well.…”
Section: Safety Issues: Pathological Gambling and Related Impulse Conmentioning
confidence: 99%
See 3 more Smart Citations